Indication of syntax on meanings by Sharif Al Mabani analysis - a grammatical study in Al-Nuzha Al-Bahiya book explaining Al-Arbaeen - Waqqas Saadi Gharkan Al Ammar, (Journal of Alsalam University, 2022)
There are texts that the more time passes, the more they become more generous and beneficial, and the one who learns them increases in care, and you find them newer, more fresh, more vegetative, and fresher water. Because of the interrelationship between the two in the curriculum, his speech (may God bless him and grant him peace) is one of the most eloquent of speech, and his style is one of the most sublime methods after the Holy Qur’an, distinguished by the abundance of material and the richness of words, and he had a great impact on preserving the language, its dialects and its strangeness, and in enriching it with its sounds and words. , and its structures, and in its documentation and protest. Imam al-Nawawi (may God have mercy on him) chose a valid sentence from the origins of the Sunnah and hadiths of rulings known as (the forty al-Nawawis), and scholars have received these hadiths with acceptance, so there are many explanations on these hadiths. The hadiths, and the explanation of Sheikh al-Qaisi was distinguished by two things, the first: he took a new way of explaining, which is the method of assumption in the question and answer, and the second: he mentioned Arabic issues for each issue, and most of his instructions in the explanation are in agreement with what was mentioned before by the rest of the commentators, and he may elaborate on them in some places. In his explanation, the explainer realized the importance of syntax and meaning and the relationship between them in the way the rules and interpretation were presented, so he employed them in understanding the meaning intended by the grammatical guidance of the words of the Prophet (may God bless him and grant him peace